The Human Skull - Claire Kirchhoff; Elizabeth Nelson (Association of American Medical Colleges, 2014)
Abstract Introduction This learning module teaches anatomy of the human skull. This module was developed because the basic anatomical knowledge of the human skull may be considered a self-study activity at certain institutions, and existing resources may not adequately convey all necessary information. Methods The module consists of a number of self-guided quizzes in PowerPoint (with answers on the following slide), using original photography of real human skeletal material. The module may be used when introducing skull anatomy during human gross anatomy with lab component. It is meant to be used in conjunction with study of real human skulls, either in preparation for hands-on study, in review of lab activities, or both. It may be used entirely as an independent study module, or with an hour of contact time with an instructor who uses a document camera to demonstrate on a real skull in a lecture hall or lab setting. It may also be used to answer student-driven questions, and work through selected practice questions. Results Students in their first year of medical school, as well as students enrolled in a medical science master's degree program sat for exam questions based on the material from this module. Overall, students performed very well on exam questions covering this material, suggesting that the learning module adequately prepared students for their exams. Results from the exam questions suggest that students found the exam material related to this learning module relatively easy. Discussion This learning module teaches anatomy of the human skull. Although this module cannot replace the study of real human skeletal material, it is designed to provide effective instruction on the human skull, and will help prepare students for future hands-on learning experiences.